Scaffolding Learner Puzzling in Exploratory Practice: Perspectives From the Business English Classroom (2018)
This study describes a teacher-researcher’s experience of scaffolding his business English learners in identifying, formulating, and exploring language learning puzzles using the principles of exploratory practice. Adopting both qualitative and quantitative methods, the teacher-researcher reflected upon the learner-initiated and learner-centred inquiry as it played out in his UK university setting. Learners’ perspectives revealed an enthusiasm for puzzling, especially when connections were established with their wider world. However, tensions also emerged, including the opaqueness of the scaffolding role and the mind-set shift required from learner-researchers and the teacher-researcher alike. Practical recommendations for teacher-researchers in similar contexts are provided: the need to highlight connection-building between learner puzzles and learners’ wider lives and the importance of recognising distinctions between puzzles and problems.